La formazione incorporata nei contesti lavorativi - Torlone, Francesca (Studies on Adult Learning and Education, 2021)
Learning devices can be embedded into organizational contexts. Through them learning processes can be intentionally activated as to transform employees while working. Workplaces have their own learning potential due to their high level of structuring and regulation. Their learning potential transform organizational actors while they are in the productive actions. Identifying embedded learning processes helps in intercepting learning valencies of workplace experiences and observing learning actions that can lead to transformative processes. Results of related research activities are presented in the volume. They have been carried out in more than ten years of research implemented in three types of organisations: business, museum, prison. Research experiences are analysed by using a model of study that is based on the reconstruction of the learning processes as they are experienced by the actors considered. Moreover the model is based on the analysis of learning actions that are embedded into the productive and service provision processes. Factors and conditions are analysed as well through which organisations can act on employees transformation.